Atención domiciliaria de la persona anciana: una perspectiva bioética (2009)
Home care for the elderly is becoming increasingly common. This creates certain problems that are directly dependent on the patient¿s longevity, pathology and the attitude assumed by the patient¿s family members or caregivers. The article examines the facts of this situation from the standpoint of bioethics, in an effort to propose changes in the attitudes adopted towards the elderly who are cared for at home.